Referral of reference names in Arabic grammar (Journal of the College of Basic Education, 2022)
Introduction :In the Name of God, the Most Gracious, the Most Merciful. Praise be to God, Lord of the Worlds, and prayers and peace be upon the master of the Messengers, Muhammad, may God’s prayers and peace be upon him, his good and pure family and his chosen companions.And after: Referring the nouns of the sign is one of the means of cohesion of the text, as it plays a prominent role in linking the pillars of the saying and the sentences to each other, which makes them important elements of the elements of the consistency and harmony of the text, as the referred to in previous words comes before the utterance of the name of the sign, so the reference is to something that exists In contrast to this referential link that is achieved for the nouns of the sign within the text, the researchers put them in what they called signs, which combine all the elements that refer directly to the external denominator, in terms of the presence of the speaking self, time or place,